Att göra en enspråkig definitionsordbok mer produktionsinriktad-exemplet Nationalencyklopedins ordbok - Malmgren, Sven-Göran (Nordiske Studier i Leksikografi, 1997)
Two kinds of ’word on the tongue’ -situations are discussed. In the first case, the speaker/dictionary user is looking fora word having a special, well-defined relation toa given word (a basic lemma). In the second case, he knows the sense ofthe word he is looking for, but there is no basic lemma to start out from. In both cases, the possibilities of CD-ROM-dictionaries to lead the dictionary user to the right word are emphasized.